Performance of SLEDAI-2K to detect a clinically meaningful change in SLE disease activity: a 36–month prospective cohort study of 334 patients. (April 2019) - Jesus, D; Rodrigues, M; Matos, A; Henriques, C; Pereira da Silva, J A; Inês, L S
Objective: The objective of this paper is to evaluate the performance of the Systemic Lupus Erythematosus Disease Activity Index (SLEDAI-2K) in detecting clinically meaningful changes in SLE disease activity. Methods: A longitudinal cohort study was conducted of 334 SLE patients during a 36-month follow-up. At each outpatient visit, disease activity was scored using the Physician Global Assessment (PGA) and SLEDAI-2K. Correlations between PGA and SLEDAI-2K were assessed. A clinically meaningful change in SLE disease activity was defined as a ΔPGA ≥ 0.3 points from baseline. Performance of SLEDAI-2K in detecting a clinically meaningful worsening or improvement was tested using receiver operating characteristic (ROC) analysis. Results: Adjusted mean PGA and SLEDAI-2K scores presented a high correlation (rho = 0.824, p  < 0.0005). In ROC analysis, a SLEDAI-2K variation presented an area under the curve (AUC) of 0.697 (95% confidence interval (CI) (0.628–0.766), p  < 0.0005) to detect a clinically meaningful improvement, with a sensitivity of 28.8% for a SLEDAI-2K ≥ 4 reduction. The AUC to detect a clinically meaningful worsening was 0.877 (95% CI (0.822–0.932), p  < 0.0005), with a sensitivity of 35.3%. Conclusions: SLEDAI-2K has a limited ability to detect clinically meaningful changes in SLE disease activity, failing to identify almost two-thirds of cases judged as having a clinically meaningful improvement or worsening. There is a need for more sensitive SLE disease activity measures in clinical practice and research.